Complementary irrigation in a maize silage double crop using the BAHICU software: a case study in Northern Buenos Aires, Argentina - Lopresti, Mariano Francisco; Bertin, Oscar Dario (2018)
The north of Buenos Aires province, in the Argentine Humid Pampa, is predominantly an agricultural region, where crops are grown mainly under rain fed conditions. However, in recent decades, complementary irrigation has been growing exponentially. The irrigated area in Buenos Aires province increased 124% between 2002 and 2012 [1]. Given the climatic characteristics of the study area, the greatest water deficit occurs in November, December and January, and thus irrigation is mainly used in summer crops. Maize is the most irrigated crop in the region due to hybrid seed production. About 90% of Argentine seed companies are located on a 180-km axis between the cities of Pergamino and Venado Tuerto (north of Buenos Aires province and south of Santa Fe province, respectively) [2]. Maize has a high potential of biomass production, with a lower water use efficiency (WUE) than other C4 summer crops like sorghum [3,4], which makes it highly sensitive to irrigation.